How Does Customer Personality Shape Customer-Employee and Customer-Firm Interactions? - Ho, Shirie Pui Shan; Chow, Matthew Yau Choi (Archives of Business Research, 2022)
In recent decades, the banking industry has undergone several changes implying the need for banks to differentiate themselves This research examines the effect of the Big Five on relationship quality and customer loyalty on both employee and firm levels in retail banks. A total of 210 online surveys were collected via the convenient sampling method. The findings showed that openness to experience, extroversion and neuroticism influence relationship quality on both levels. Conscientiousness affects relationship quality at the bank level while agreeableness affects relationship quality at the customer contact employee level. Relationship quality displayed significant influence on customer loyalty on both levels. Several implications are derived for service research and service encounter management. The findings provide valuable insight for matching retail bank customers and customer-contact employees based on their personality profiles to ensure long-term relationship quality and customer loyalty. Insights into the relationship quality-customer loyalty link can act as a starting point for academics who are interested in understanding the role of frontline employees in services management.